Influence of pelvic position on shoulder range of motion - Bishoy S. Lobbos; Mohamed M. M. Essa; Alaaeldin Khaireldin; Mohamed Y. Gamal El-Din; Phillips Rizkallah; Heba Allah Samy (BMC Musculoskeletal Disorders)
Abstract Background pelvis and shoulder are deeply integrated. They are connected by myofascial slings. The pelvic and spinal posture affects the position of the scapula and the activity of its muscles and affects acromio-humeral distance and so that affects shoulder movement. The aim of the study was to investigate the influence of pelvic position on the shoulder range of motion. Methods The full active range of motion (flexion/extension, abduction, and external/internal rotation) of both shoulders was measured by digital goniometer for 33 normal adult subjects. Measurements were taken from a standing position in the following pelvic positions: 1- Neutral posture, 2- Evoked anterior and posterior pelvic tilt, 3- Evoked right and left pelvic rotation, 4- Evoked right and left lateral pelvic tilt. For every shoulder movement, One-Way ANOVA including Tukey post hoc test was used to compare between different positions. Results Anterior pelvic tilt leads to a significant increase in flexion and a significant decrease in extension of both shoulders (P value was < 0.001). Posterior pelvic tilt leads to the opposite. Pelvic rotation leads to a significant decrease in shoulder flexion on the same side of rotation and shoulder extension on the opposite side of rotation (P value was < 0.001). Lateral pelvic tilt leads to a significant decrease in abduction on the same side of lateral tilt (P value was < 0.001). Conclusion pelvic position affects shoulder range of motion.